Strategi Pengembangan Budidaya Jamur Tiram sebagai Komoditas Pertanian di Perkotaan - Rusadi, Ni Wayan Purnami (Department of Agribusiness Halu Oleo University Kendari Southeast Sulawesi, 2020)
This study aims to determine the most effective priority strategy to be applied in developing oyster mushrooms as an Agricultural Commodity in Urban City (Case Study of Oyster Mushroom Farmers in Denpasar City). The location selection method in this study was purposive. Stages of the study include the identification of internal factors, namely strengths and weaknesses, and external factors, namely the opportunities and threats faced by oyster mushroom farmers in Denpasar. The input stage is carried out by creating an IFAS matrix and an EFAS matrix. The matching stage uses the SWOT matrix and the decision stage uses QSPM. The results showed an alternative strategy obtained, namely improving the quality of products ranging from seedlings (F1), baglog (growing media), and oyster mushrooms; Form partnerships with baglog makers so they can reach price agreements; Form partnerships between fellow mushroom farmers so they can work together in the distribution of crops; Form partnerships with the oyster mushroom processing industry so that farmers get stable selling prices; Government programs to increase the capacity of mushroom cultivation for the community in a sustainable manner; Organizing a production and marketing management training program; Conducting oyster mushroom cultivation workshops for the general public; Improving environmental sanitation for making baglog or mushroom cultivation; Conduct training on post-harvest handling and waste generated after cultivation. The priority strategy obtained in the development of oyster mushrooms in the city of Denpasar is to conduct training on handling post-harvest and post-cultivation waste produced with a value of 11,590.